Academic self-regulation as a bridge between mindfulness and emotional self-efficacy among undergraduate students - Samer Adnan Abdel Hadi; Mahmoud Alquraan (Institute of Advanced Engineering and Science, 2026)
The research investigated the function of academic self-regulation as a mediator in the correlation between mindful attention awareness and emotional self-efficacy. A quantitative questionnaire-based study approach was used. A total 647 undergraduate participants (77.1% female), aged 18–24 (74.5%), completed self-report questionnaires, including the mindful attention awareness scale (MAAS), the academic self-regulation scale (ASRS), and the emotional self-efficacy scale (ESES). The proposed model demonstrated acceptable global fit based on the two-index criteria applied in this study, with RMSEA meeting the ≤0.06 threshold and SRMR meeting the ≤0.09 threshold; based on the data, the model appears to be suitable. The findings indicated statistically significant relationships between mindfulness and the subscales of academic self-regulation: self-instruction and self-evaluation. Academic self-regulation showed significant path coefficients with emotional self-efficacy: self-planning, self-monitoring, and self-reaction were statistically significantly associated with using and managing one’s own emotions and perceiving emotions through facial expressions. Self-planning and self-monitoring were statistically significantly associated with dealing with emotions in others. Self-planning, self-monitoring, self-instruction, and self-reaction were statistically significant in their association with identifying and understanding one’s own emotions. Academic self-regulation elucidates the correlation between mindfulness and emotional self-efficacy. Emotional self-efficacy and well-being can be bolstered by improving mindfulness and self-regulation.